2021
DOI: 10.1002/jsfa.11109
|View full text |Cite
|
Sign up to set email alerts
|

A positive effect of egg consumption on macular pigment and healthy vision: a systematic review and meta‐analysis of clinical trials

Abstract: Increasing macular pigment optical density (MPOD) as a result of increased macular concentration of lutein and zeaxanthin may reduce the risk of age‐related macular degeneration (AMD). The aim of the present study was to determine whether the consumption of eggs, a rich source of dietary lutein and zeaxanthin, influences MPOD and serum lutein. In this systematic review and meta‐analysis we searched PubMed, Scopus, and ISI Web of Science up to July 2020, for relevant randomized clinical trials. Using a random‐e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The effect of egg consumption on vision has been poorly investigated. The results of a recent meta-analysis of dietary intervention studies showed that the intake of eggs (range 1–4 eggs per day, duration 5–48 weeks) increased macular pigment optical density and serum lutein concentrations by reducing AMD progression [ 40 ]. However, the small number of studies ( n = 5), few participants in them ( n = 296), and their moderate quality could not allow any definitive conclusions, as remarked in [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of egg consumption on vision has been poorly investigated. The results of a recent meta-analysis of dietary intervention studies showed that the intake of eggs (range 1–4 eggs per day, duration 5–48 weeks) increased macular pigment optical density and serum lutein concentrations by reducing AMD progression [ 40 ]. However, the small number of studies ( n = 5), few participants in them ( n = 296), and their moderate quality could not allow any definitive conclusions, as remarked in [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because egg is a rich source of lutein and zeaxanthin, two carotenoids that largely maintain macular pigment function, there has been interest in the impact of egg intake for the prevention of age-related macular degeneration, which leads to loss of vision. A recent meta-analysis of five RCTs concluded that egg intake may reduce the progression of age-related macular degeneration (74). However, some of the studies used lutein-enriched eggs and when the analyses were stratified by the intervention type (normal eggs or lutein-enriched eggs), the results did not reach statistical significance anymore.…”
Section: Data Gaps For Future Researchmentioning
confidence: 99%
“…As known, Ax and lutein can be spread through the food chain. Animal-derived foods, including chicken eggs, salmon, and trout, although not usually the most abundant sources of Ax and lutein for humans, contain highly bioavailable and stable pigments ( Bunger et al., 2014 ; Khalighi et al., 2021 ). Astaxanthin or lutein-enriched eggs have been found to increase their serum contents and mitigate hypertension ( Bunger et al., 2014 ; Hatabu et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%